PERAN KANAL ONLINE DALAM EDUKASI PRANIKAH - Farid, Diana; Pakarti, Muhammad Husni Abdulah; Saepullah, Usep; Hendriana, Hendriana (FASTABIQ: JURNAL STUDI ISLAM, 2022)
Today's phenomenon is very concerning, because a lot of young people seem to be hasty in making the decision to rise. It is undeniable that deciding to get married today is just a trend, or a mere worry/fear, without being based on self-debriefing, material and insight into how to live a life after marriage. In addition, these concerns plus the lack of premarital education, whether it is from the government or media channels, there are very few media lizards that provide educational content related to premarital. This article intends to describe the role of online media as a virtual channel of premarital information and guidance. The research method used is a descriptive method with a qualitative approach and data collection techniques obtained by interviews and documentation. Based on the results of research that has been carried out on the function of social media channels in premarital education, there are three roles, namely first, social media channels act as premarital education media to become a message of proselytizing. Second, social media channels as a medium that transmits premarital education into proselytizing messages and insights and the third serves as a reference or source of premarital education for people who need references related to this matter. The result is that today's social media channels are very effective in educating the public through online media channels to provide premarital education, because these contents are very much needed for netizens today to at least provide an overview of the world after deciding on a marriage.Keywords: online pre-wedding education, pre-wedding content, social media channels